INTEGRASI MATEMATIKA DAN ISLAM DALAM PEMBELAJARAN MATEMATIKA - Mubarok, Alfian (Jurnal Ilmiah Pendidikan dan Keislaman, 2021)
Learning mathematics should be amended in the context of improvement of the quality of education so as to enhance the optimal learning outcomes. Therefore, efforts continue to be made to the realization of an innovative learning in accordance with the times and technology. Besides education aligned with technological advances, education is also expected to build the value and character of each learner through the values agama.Al-Quaran the holy book of Islam that is the source of all sources of knowledge. Greatness will not be incomparable and was nevertheless timeless. By karenaya we as Muslims should and it becomes imperative to make Al-Quran as the main reference for the development of science before referring to theories or concepts sharing. Such a view is not wrong because the Koran is very influential in the development of science. It is clear that there are very tinggibagi award those who believe and knowledgeable than those with ordinary saja.Hal is showing Koran is very concerned with the development of science. Therefore, it is important the world of education is no exception in mathematics learning integrates the values contained in the religion of Islam in every lesson. Thus, in addition to studying math students can also learn the majesty of Allah through mathematical approach to materials.